2018
DOI: 10.1111/pbi.13015
|View full text |Cite
|
Sign up to set email alerts
|

Variation in abundance of predicted resistance genes in the Brassica oleracea pangenome

Abstract: Brassica oleracea is an important agricultural species encompassing many vegetable crops including cabbage, cauliflower, broccoli and kale; however, it can be susceptible to a variety of fungal diseases such as clubroot, blackleg, leaf spot and downy mildew. Resistance to these diseases is meditated by specific disease resistance genes analogs (RGAs) which are differently distributed across B. oleracea lines. The sequenced reference cultivar does not contain all B. oleracea genes due to gene presence/absence v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 109 publications
4
110
1
Order By: Relevance
“…In a previous study, Bayer et al . () reported that in B. oleracea, core genes had more low‐ and moderate‐impact SNPs than variable genes, while core genes and variable genes showed almost identical numbers of high‐impact SNPs. Our result is different from that previously reported in soya bean, where the variable genes in the soya bean pangenome have a higher proportion of SNPs (Li et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In a previous study, Bayer et al . () reported that in B. oleracea, core genes had more low‐ and moderate‐impact SNPs than variable genes, while core genes and variable genes showed almost identical numbers of high‐impact SNPs. Our result is different from that previously reported in soya bean, where the variable genes in the soya bean pangenome have a higher proportion of SNPs (Li et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The pangenome size was 1044 Mbp and contained 1749 predicted R-genes. Gene PAV discovery was performed using the SGSGe-neLoss package (Golicz et al, 2015) as described in Hurgobin et al (2018) and Bayer et al (2018).…”
Section: Pangenomementioning
confidence: 99%
See 2 more Smart Citations
“…In the plant kingdom, the family Brassicaceae holds a great agronomic, scientific and economically important position and comprises more than 372 genera and 4060 species [2]. Of the diverse species, Brassica oleracea (CC, 2n = 18) constitutes well defined group of economically and nutritionally important morphotypes, referred to as cole vegetables (kale, kohlrabi, cabbage, cauliflower, broccoli, brussels sprout) [52].…”
Section: Introductionmentioning
confidence: 99%